Smart RFID and IoT-Based Patient Monitoring Systems in Modern Healthcare - Yadav, Balkrishna Rasiklal (International Journal of Engineering and Management Research, 2024)
Radio Frequency Identification (RFID) is used to identify the characteristics of an object wirelessly using radio waves. This project combines the power of RFID technology with real-time health monitoring in a hospital setting. Utilizing RFID tags for patient identification and asset tracking, the system seamlessly integrates with temperature sensor, blood pressure sensor and SpO2 sensor. The collected data is then transmitted to an Internet of Things (IoT) platform for continuous monitoring. The system not only ensures accurate patient identification and efficient asset management, but also provides real-time oxygen saturation, blood pressure rate and temperature data. This information is displayed on the LCD screen, offering healthcare professionals immediate insights into patient health. This innovative solution enhances patient care, promotes proactive medical interventions, and exemplifies the IOT in advancing healthcare.